2020
DOI: 10.3390/f11101081
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Season on Productivity and Time Consumption in Timber Harvesting from Young Alder Stands in Lowland Poland

Abstract: The purpose of this study was to establish the impact of season on productivity, labour consumption, and working time structure during timber harvesting from young alder stands (Alnus glutinosa Gaertn.). An early thinning process was performed in summer and winter in pure alder stands (38 and 40 years old) in the Płaska Forest Division (NE Poland). The felling and processing operations were performed by experienced loggers using the cut-to-length (CTL) system, and forwarding with manual loading and unloading i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
2
8
1
1
Order By: Relevance
“…Although the current study confirms that both slope gradients and weather conditions affected the felling productivity and the cost, this is not always straightforwardly the case. This result is not consistent with the findings of Grzywi ński et al [18], in which felling productivity rates were similar in winter (snowy) and summer (sunny) in ground-based harvesting operations.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Although the current study confirms that both slope gradients and weather conditions affected the felling productivity and the cost, this is not always straightforwardly the case. This result is not consistent with the findings of Grzywi ński et al [18], in which felling productivity rates were similar in winter (snowy) and summer (sunny) in ground-based harvesting operations.…”
Section: Discussioncontrasting
confidence: 99%
“…The longer log processing time can be attributed to the large volume of hardwood stems, the variable topographic conditions, and the higher density of understory vegetation. Similar patterns were noted by Mousavi [34] and Grzywi ński et al [18], who found that 58% of the labor time was spent during felling and processing in a ground-based harvesting operation.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is mainly necessary for calculating cost calculations or employee salaries. Detailed time studies allow to evaluate the performance of forest machine operators [1], to identify problems associated with work in night shifts [2], to develop productivity forecasting models, to find the most suitable logging machines for specific types of felling and work conditions [3], [4], and to compare seasonal variations of productivity [5].…”
Section: Introductionmentioning
confidence: 99%